A blockchain-based NFV market in the multi-node edge computing network. (29th March 2023) - Jiang, Suhan; Wu, Jie
Currently, network function virtualisation (NFV) incorporates cloud computing (CC) and forms a market, providing elastic and cost-efficient chained network services. This paper considers a new NFV market in edge computing, where NFV providers deploy service chains on near-by EC nodes instead of remote data centres. An optimisation problem is formulated to minimise the deployment costs of a required service chain from an NFV provider's perspective, with user service delay guarantees. Due to its NP-hardness, we investigate two special network models, where we can turn to dynamic programming solutions. We propose a pricing mechanism based on bargaining theory to decide fair resource prices for EC nodes. To relinquish the full power of the NFV provider, we design a blockchain-based system to implement our algorithms using smart contract. Simulations are conducted and numerical evaluations are presented to demonstrate the efficiency of our solutions and the applicability of our system.